2019
DOI: 10.3390/f10010034
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Short Forest Recreation Program on Physiological and Psychological Relaxation in Young Polish Adults

Abstract: Forest recreation is an activity that could be successfully used to alleviate negative symptoms of stress in individuals. Multiple positive psychological and physiological effects have been described in the literature, especially regarding works describing research from Asian countries such as Japan, Korea, and Taiwan. In East-Central Europe, however, the effectuality of forest recreation has not been addressed in scientific research. Thus, a special recreation program was developed, and its usability was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 47 publications
(73 reference statements)
5
72
0
2
Order By: Relevance
“…Anxiety levels, measured using the STAI-S questionnaire, significantly decreased. These findings are consistent with studies that tested the effect of forest therapy on healthy Polish young adults [31,36] and found that some indicators of negative mood decreased after exposure to a forest environment. These findings are in opposition to those described in the work of Bielinis et al [31], in which healthy Polish young adults were tested and only one negative mood indicator, fatigue, increased significantly (mean pre-test = 1.61; mean post-test = 0.80).…”
Section: Patients With Affective Disorderssupporting
confidence: 91%
See 2 more Smart Citations
“…Anxiety levels, measured using the STAI-S questionnaire, significantly decreased. These findings are consistent with studies that tested the effect of forest therapy on healthy Polish young adults [31,36] and found that some indicators of negative mood decreased after exposure to a forest environment. These findings are in opposition to those described in the work of Bielinis et al [31], in which healthy Polish young adults were tested and only one negative mood indicator, fatigue, increased significantly (mean pre-test = 1.61; mean post-test = 0.80).…”
Section: Patients With Affective Disorderssupporting
confidence: 91%
“…In affective inpatients, perhaps fatigue is difficult to change via a forest recreation programme, whereas in healthy adults, it is more variable. In another study by Bielinis et al [36], changes in fatigue levels of working or studying healthy young adults were only marginally nonsignificant (p = 0.084, large effect size) and decreased after exposure to a forest environment (mean pre-test = 1.22; mean post-test = 0.81), supporting this suggestion. In other studies, in which psychiatric inpatients were examined, no significant effects of forest therapy on mood states were found, but in these studies lower numbers of participants were tested (10 patients in experimental group and 10 in control group).…”
Section: Patients With Affective Disordersmentioning
confidence: 84%
See 1 more Smart Citation
“…Third, only psychological measurements were used in this case; the physiological effects of this activity were not considered [44].…”
Section: Limitationsmentioning
confidence: 99%
“…To this end, the traditional and alternative values of the forest providing various management objectives should address the integration of all its functions, including timber, biodiversity, protection from soil erosion and floods, and carbon sink, as well as its recreational services [24]. Recent findings revealed the positive effects of forest recreational activities in mental health and psychological and physiological wellbeing ("forest bathing") [25,26], which declares the need for the engagement and further development of forest recreation schemes and infrastructures. Tourism growth is highly dependent on infrastructures, such as the road network, transportation, accessibility amenities, and hotels, provided in the destination, while it is also appraised that infrastructural development influences local people in a positive way towards tourism development [27].…”
Section: Introductionmentioning
confidence: 99%